Primum non nocere. Stanowisko środowiska medycznego wobec problemu aborcji a jego relacje z Kościołem w okresie Wielkiej Nowenny (1956–1966) - Jarkiewicz, Katarzyna (Pamięć i Sprawiedliwość, 2017)
The backward treatment during the Stalinist period in 1956 was set against the need to stop uncontrolled abortions. The liberalization of the abortion law was supposed to solve the swollen social problems with the hands of doctors who had been assigned the duty to perform abortions without limitation. Doctors, who are attached to the ethical standards of the profession, sabotaged the law, demanding to keep in this matter the freedom of decision and the principle of “primum non nocere”. Communist authorities applied repression against the resistance, especially after exacerbation of abortion procedures in 1959. They removed the gynecologists, who were protesting against the dictatorship of administrative decisions, or demanded a change of specialization. The protector of the repressed was the Church, who opposed the secularization of the health service and during the Great Novena, he organized for medics the professional pastoral care integrating their (pilgrimages to Jasna Góra, training of natural methods of conception regulation, lectures on ethical principles). Despite the efforts made by the medical community, the communist authorities have introduced medicalisation of obstetrics and have limited the Church’s influence on hospital care. They removed the nuns from the healthcare system and imposed doctors instead of the medical code on the set of mandatory administrative procedures. The result of the actions taken was the complete subordination of the health service to the ideological goals.